Community-based antiretroviral therapy (ART) delivery for female sex workers in Tanzania: intervention model and baseline findings. Issue 6 (2nd June 2020) - Vu, Lung; Tun, Waimar; Apicella, Louis; Casalini, Caterina; Makyao, Neema; Tsang, Samantha; Michael, Denna; Koppenhaver, Todd; Mlanga, Erick
ABSTRACT: To increase linkage to and retention in antiretroviral therapy (ART) care, we piloted a community-based, ART service delivery intervention for female sex workers (FSWs). At baseline, we recruited and collected data from 617 FSWs (intervention: 309; comparison: 308) who were HIV positive and not on ART. This paper presents (1) the description of the intervention model, and (2) key descriptive and bivariate-level findings of the baseline FSW cohort. The data showed more than half of FSWs had a non-paying sex partner, and less than one-third used a condom at last sex with paying and non-paying clients, which suggest potentially high levels of HIV transmission. In addition, there is a gap in HIV testing and treatment because one-third learned about their HIV-positive status only at study enrollment, and among FSWs who had known their status for more than a month, half had not registered in care. This substantiates the importance of timely HIV diagnosis and treatment. A community-based ART program may serve as an important strategy in closing the HIV care and treatment gap for FSWs.